Analisis Bibliometrik Sistem Peradilan Pidana Indonesia - Rahmiati (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study aims to analyze the development and trends of academic studies on the criminal justice system in Indonesia using a bibliometric approach. This approach is used to identify author contributions, institutional affiliations, and key keywords that often appear in scientific publications and map the relationships between elements. Three visualization methods used to answer the research questions are Three-Field Plot (RQ1), TreeMap (RQ2), and WordCloud (RQ3). The analysis focuses on documents published between 2020 and 2025 to be relevant to current developments, including technological advances such as blockchain. Data were analyzed using R Studio software. The results of this study indicate the dynamics of scientific contributions that continue to grow over time. Through interactive visualization, complex information about the research landscape can be presented more understandably, thus useful for policy development and future research. The limitation of this study lies in the number of Scopus databases obtained. Further research is recommended to search for other keywords and compare between leading databases such as WOS and Google Scholar